VV-ECMO for surgical cure of a critical central airway obstruction. (2019) - Raza, Hassan A.; Nokes, Brandon T.; Jaroszewski, Dawn; Garrett, Ashley; Sista, Ramachandra; Ross, Jeffrey; Farmer, Joseph C.; Lyng, Philip J.
Abstract: Extracorporeal membrane oxygenation (ECMO) is a form of prolonged cardiopulmonary bypass that has extensively been used in critically ill patients in an intensive care setting. Both veno-venous (VV-) and veno-arterial (VA-) ECMO have been described as a perioperative rescue or replacement of endotracheal intubation in the setting of extrinsic airway compression due to a mediastinal mass. In this paper, we will outline the utility of ECMO in the context of extrinsic airway compression and will use an illustrative case to examine how ECMO can be useful during severe airway obstruction. Our patient successfully underwent surgical resection of the mass while on VV-ECMO. His symptoms resolved quickly and is now back to his baseline quality of life.